MVA SEBAGAI PROXY EVA DAN PENGARUHNYA PADA NOPAT DAN TOTAL SHAREHOLDER RETURN– PERUSAHAAN ECERAN TBK - Priyo Darmawan (Jurnal Akuntansi Bisnis, 2017)
The development in the Indonesian capital market, both in depth and breadth along with the increased awareness among the shareholders, has increased the pressure on the companies to consistently perform better. One of the indicators of such performance is the Market Value Added (MVA). Literature is replete with studies, which have tried to capture the behavior of MVA. Stewart (1991) claims that EVA is the ultimate proxy of MVA. Following Stewart (1991), several studies examined the relationship between EVA and MVA using the Stern Stewart-1000 data. Most of these studies found evidence to support Stewart’ s  claim. Despite the popularity of the concept, very few studies have been undertaken to empirically test the ability of EVA to reflect or proxy the MVA of Indonesian retail  companies, which registered on the Indonesia Stock Exchange from 2002 - 2006. This study makes an attempt to fill the gap. This study empirically examines the relationship between MVA and EVA of the Indonesian retail go public companies. Though the focus of the paper is the relationship between EVA and MVA, it also tries to understand the relationship between MVA and other common accounting numbers like NOPAT, TSR. The study indicates that there is no strong evidence to support Stern Stewart’ s claim that EVA is superior to the traditional performance measures in its association with MVA.Key Words: Economic Value Added (EVA), Market Value Added (MVA), Net Operating Profit after Tax (NOPAT), Total Shareholder Value (TSR)